THE EFFECT OF THE MENSTRUAL CYCLE ON RENIN, ALDOSTERONE AND ALDOSTERONE-TO-RENIN RATIO IN FORMERLY PREECLAMPTIC AND HEALTHY WOMEN. (April 2021) - Alnazer, Rawan; Veldhuizen, Gregory; Spaanderman, Marc; De Leeuw, Peter
Abstract: Objective: The aldosterone-to-renin ratio (ARR) is widely used as a screening test for primary aldosteronism (PA) in patients with hypertension. The purpose of the present original investigation is to identify the impact hormonal changes have on renin, aldosterone, and the ARR during the menstrual cycle of premenopausal women when measured in strict standardised conditions. Design and method: We analysed 59 women with a history of preeclampsia and 6 healthy parous controls. Blood values were determined during both follicular and luteal phases of the menstrual cycle (days 1 and 14 respectively). Plasma aldosterone, active plasma renin concentration (APRC) and the ARR were measured under standardised conditions. All measurements were taken in the supine position at 9am, all patients maintained a standardised sodium diet (100 mmol/day) for no less than two weeks. In those who were receiving antihypertensive medications (n = 2), all medications were discontinued at least 1 week prior to screening. Results: When performing the Friedman's Test and the Wilcoxon signed rank test in formerly preeclamptic women (n = 59), aldosterone and renin were both significantly elevated in the luteal phase (mean rank aldosterone 1.2 and 1.8 p0.000 Z-4.7, mean rank renin 1.23 and 1.77 p0.000 Z -4.5, respectively), however the ARR values did not significantly differ between phases (mean rank 1.53 and 1.47 p0.7 Z-0.14). When performing the Friendman's Test in the control group (n = 6), the difference in aldosterone, renin and the ARR between the follicular and luteal phase was not significant (p0.059 for all parameters). Wilcoxon signed test revealed a significant difference in aldosterone (Z-2.02 p0.04), but the difference in renin and the ARR remained insignificant (p0.06). Conclusions: In this study of premenopausal women we found that both renin and aldosterone are significantly affected by the menstrual cycle. However the resulting ARR was not statistically significantly altered. Our study indicates that it is not necessary to take the menstrual phase of patients into account when performing and interpreting the ARR as a screening test for PA in patients with a history of preeclampsia.